Trends in utilization of sentinel node biopsy and adjuvant radiation in women ≥ 70. Issue 7 (6th January 2020) - Gunn, Jinny; Lemini, Riccardo; Partain, Kristin; Yeager, Tamanie; Almerey, Tariq; Attwood, Kristopher; McLaughlin, Sarah; Bagaria, Sanjay P.; Gabriel, Emmanuel
Abstract: Background and Objectives: Omission of routine axillary staging and adjuvant radiation (XRT) in women ≥ 70 years old with early stage, hormone receptor‐positive, clinically node‐negative breast cancer has been endorsed based on several landmark studies. We sought to determine how much omission of axillary staging/XRT has been adopted. Methods: Using the National Cancer Data Base, we selected malignant breast cancer cases in women ≥ 70 with ER + tumors, ≤2 cm with clinically negative lymph nodes who underwent breast conservation and had known XRT status in 2005‐2015. The use of sentinel lymph node biopsy (SNB) and XRT status was summarized by year to determine trends over time. Results: In total, 57 230/69 982 patients underwent SNB. Of the 12 752 patients in whom SNB was omitted, 6296 were treated at comprehensive community cancer programs. Regarding XRT, 33 891/70 114 received adjuvant XRT. There were no significant trends with regards to patients receiving SNB or those receiving XRT. Conclusion: Since 2005, there has been no change in SNB or XRT for early stage ER + breast tumors. However, there was a difference in omission of SNB based on facility type and setting. Future monitoring is needed to determine if these trends persist following the recently released Choosing Wisely ® recommendations.